2019
DOI: 10.1177/0003489419884337
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Medical Scribes on Patient Satisfaction in an Academic Otolaryngology Clinic

Abstract: Objectives: Evidence shows that scribes can improve provider efficiency and satisfaction in several settings, but is mixed on whether scribes improve patient satisfaction. We studied whether scribes improved patient satisfaction in an academic otolaryngology clinic. Methods: The authors performed a retrospective review of patient responses to the Press Ganey survey between 12/2016 and 12/2017. Their responses about satisfaction with the provider and wait times were examined. Three providers worked with scribes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…15,16,28,30,[32][33][34]39,50 Of these 9 studies, 7 of them 15,16,28,[32][33][34]50 reported higher provider satisfaction with a scribe, whereas 2 of 9 studies 30,39 reported no difference. Seven studies 18,20,23,36,45,49,51 reported provider satisfaction specifically with scribes without a comparator, and all results were supportive of scribes.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…15,16,28,30,[32][33][34]39,50 Of these 9 studies, 7 of them 15,16,28,[32][33][34]50 reported higher provider satisfaction with a scribe, whereas 2 of 9 studies 30,39 reported no difference. Seven studies 18,20,23,36,45,49,51 reported provider satisfaction specifically with scribes without a comparator, and all results were supportive of scribes.…”
Section: Resultsmentioning
confidence: 97%
“…Thirty-nine studies were included, comprising greater than 562,682 patient encounters (Table E1, available online at http://www.annemergmed.com). Five studies were randomized controlled trials, [15][16][17][18][19] 23 studies were prospective nonrandomized studies, 10 studies were retrospective, [43][44][45][46][47][48][49][50][51][52] and 1 study had both prospective and retrospective components. 53 All studies were published between 2010 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[38][39][40] Although there is likely no easy single solution, previous studies found that employment of physician extenders, the use of scribe services, and the integration of similar support mechanisms can increase the number of patients seen while demonstrating a positive benefit toward patient satisfaction and physician well-being. 41,42 A thoughtful 2016 commentary by Shanafelt and Noseworthy identified 9 organizational strategies to promote physician engagement and reduce burnout. 12 In the current study, we identified a relatively low prevalence of depression (8%) and anxiety (11%) among academic otolaryngology attending physicians, which appears slightly elevated over US adult population estimates.…”
Section: Discussionmentioning
confidence: 99%